2020
DOI: 10.3390/coatings10020158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process Conditions on the Growth and Texture of CVD Alpha-Alumina

Abstract: In the present study, the influence of experimental variables on the growth characteristics and texture development in chemically vapour deposited α-Al2O3 coatings was investigated. The emphasis was on the effects of H2S. The α-Al2O3 layers were deposited from the AlCl3-H2-CO2-HCl-H2S precursor system onto intermediate Ti(C,N) layers. The substrate was cemented carbide. The coatings were characterized with respect to microstructure and texture using X-ray diffraction, scanning electron microscopy and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 38 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…CVD coating techniques are preferred for coating SiAlON inserts because of the strength of the bonds that are created between the SiAlON substrate and the interatomic bonding layer. Previous studies [20][21][22][23][24][25] deduced that chemical vapour deposition is the most suitable method for creating thin-film coatings that have high durability and high wear resistance at high cutting temperatures. The benefit of the chemical vapour deposition coating process is that it allows for a high enough temperature to be reached on the surface of the heated substrate.…”
Section: Introductionmentioning
confidence: 99%
“…CVD coating techniques are preferred for coating SiAlON inserts because of the strength of the bonds that are created between the SiAlON substrate and the interatomic bonding layer. Previous studies [20][21][22][23][24][25] deduced that chemical vapour deposition is the most suitable method for creating thin-film coatings that have high durability and high wear resistance at high cutting temperatures. The benefit of the chemical vapour deposition coating process is that it allows for a high enough temperature to be reached on the surface of the heated substrate.…”
Section: Introductionmentioning
confidence: 99%
“…8% due to the heat generated during thermal CVD process and metal cutting [10]. It was also reported that the mechanical properties of CVD α-Al 2 O 3 coatings could be enhanced by choosing an optimized texture for the α-Al 2 O 3 phase [11]. Consequently, CVD Al 2 O 3 coatings have continuously been optimized with respect to the phase and film texture control.…”
Section: Introductionmentioning
confidence: 99%